Do You Even Crypto, Bro? Cryptocurrencies in Household Finance - Michael Weber; Bernardo Candia; Olivier Coibion; Yuriy Gorodnichenko (Institute of Labor Economics (IZA), 2023)
Using repeated large-scale surveys of U.S. households, we study the cryptocurrency investment decisions and motives of households relative to other financial assets. Cryptocurrency holders tend to be young, white, male and more libertarian relative to non-crypto holders. They expect much higher rates of returns for crypto and perceive it as relatively safer than do other households. They also view it as a better hedge against inflation. For those holding cryptocurrencies, changes in Bitcoin prices translate into their purchases of durable goods. Finally, exogenously-provided information about historical returns of cryptocurrencies leads individuals to increase their desired crypto holdings and makes them more likely to actually purchase cryptocurrency subsequently. We compare these views and behaviors to those of households toward other financial assets and argue that cryptocurrency is unique in many of these respects.
Keywords: E4; G5; D8; 330; cryptocurrency; household finance; surveys